Molecular Docking study to Identify Potent Fungal Metabolites as Inhibitors against SARS-CoV-2 Main Protease Enzyme - Dr Diptendu Sarkar (International Journal of Pharma and Bio Sciences, 2021)
Severe acute respiratory syndrome (SARS) is a viral respiratory disease caused by a SARS-associated coronavirus and SARS-CoV-2 has proven to be a pandemic worldwide. Coronaviruses are a type of enveloped virus. They are basically single-stranded and positive-sense RNA viruses which belongs to the subfamily Coronavirinae. Structure of SARS-CoV-2 is predicted to be the same as SARS-CoV due to high sequence similarity. SARS-CoV-2 is proven to be a major pandemic creator and affected the world at an exponential rate. The genome of COVID19 codes for the main protease 6LU7, is essential for viral replication and multiplication. To get a possible antiviral drug(s), nowadays is the major concern. In our study we screened ten fungal metabolites such as Aspirochlorine, Aflatoxin B1, Alpha-Cyclopiazonic acid, Sporogen, Asperfuran, Aspergillomarasmine A, Maltoryzine, Kojic acid, Aflatrem and Ethyl 3-nitropropionic acid against main protease 6LU7. These molecules were of fungal origin from Aspergillus flavus and Aspergillus oryzae. Aspergillomarasmine A exhibited the docking score of – 6.02 Kcal/mol, almost nearer to presently used drug Chloroquine (-6.29 Kcal/mol). Second highest docking score was found for Asperfuran (-5.5 Kcal/mol), whereas Aflatoxin B1 provided docking score was -5.0 Kcal/mol. We found similar docking score -5.4 Kcal/mol for Asperfuran, Maltoryzine and Kojic acid. Aspirochlorine and Ethyl 3-nitropropionic acid exhibited docking score were -5.3 Kcal/mol and -5.1 Kcal/mol respectively. These natural bioactive compounds could be tested in near future for their ability to inhibit viral growth both in invitro as well as invivo study.